Private and Public Consumption and Counter-Ciclical Fiscal Policy - Luigi Marattin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
In this paper we set up a NK-DSGE model in which the consumer derives utility from a consumption basket made of public and private consumption, there is monopolistic competiton in the intermediate good sector, Calvo-Yun price setting, endogenous labour supply and Taylor rule for monetary policy. We analyse the effects of a counterciclical fiscal policy rule and how varying the degree of counterciclicality affects the determinacy of the rational expectations equilbrium and the ability to respond to technological and government spending shocks. A broad conclusion is that desiderability of pro/counter ciclical stance of fiscal policy cannot accurately be drawn without taking into account the quality of the public expenditure and the way it interacts with private consumption.
Keywords: 330